CALL Communities and Culture – Short Papers From EUROCALL 2016 2016
DOI: 10.14705/rpnet.2016.eurocall2016.539
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of CALL to advanced-levelforeign/second language instruction

Abstract: This paper evaluates the contribution of instructional technology to advanced-level foreign/second language learning (AL2) over the past thirty years. It is shown that the most salient feature of AL2 practice and associated Computer-Assisted Language Learning (CALL) research are their rarity and restricted nature. Based on an analysis of four leading CALL journals (CALICO, CALL, LL&T, ReCALL), less than 3% of all CALL publications deal with AL2. Moreover, within this body of research, the range of languages i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In their study of "advanced" learners in major CALL journals, for example, Burston and Arispe (2016) found that 50% were at B1 and 34% at B2 levels on the Common European Framework of Reference for Languages. In our case, the intermediate category in particular seemed to include individuals who elsewhere would be ranked as lower-or upper-intermediate or even false beginner or advanced.…”
Section: Sophistication Variablesmentioning
confidence: 99%
“…In their study of "advanced" learners in major CALL journals, for example, Burston and Arispe (2016) found that 50% were at B1 and 34% at B2 levels on the Common European Framework of Reference for Languages. In our case, the intermediate category in particular seemed to include individuals who elsewhere would be ranked as lower-or upper-intermediate or even false beginner or advanced.…”
Section: Sophistication Variablesmentioning
confidence: 99%
“…It is no surprise perhaps that among the main conclusions of syntheses are recommendations for better reporting practices in primary research, as it is only at this stage that it becomes really apparent how much information is missing, vague or unsubstantiated. Burston and Arispe (2016), for example, found that 50% of research articles in four major CALL journals targeting 'advanced' levels of proficiency had learner populations of B1 level only.…”
Section: Variationmentioning
confidence: 99%
“…In recent years, the importance of practising communicative language learning competence has been highlighted in foreign language learning and teaching, together with an increased use of current technological means to facilitate communication skills. According to a study by Burston and Arispe (2016), 81% of computer assisted language studies focus on 'writing' skills of foreign language learners. While the learners' grammatical and communicational abilities could be enhanced, few studies have been focusing on the learners' enhancement of their reading, grammatical, and lexical competence.…”
Section: Introductionmentioning
confidence: 99%